Hubungan Pengetahuan dengan Perilaku Personal Hygiene saat Menstruasi pada Remaja Putri Pondok Pesantren Al Quran dan Sains Nurani Tahun 2023 - Bunga Khumairoh Azzahra; Nining Rukiah; Aisyah Safitri (Lembaga Pengembangan Kinerja Dosen, 2024)
Personal hygiene behavior is still considered less important among teenagers. This is due to teenagers' lack of knowledge regarding personal hygiene, so that personal hygiene behavior is difficult to implement in everyday life. Objective : To determine the relationship between knowledge and personal hygiene behavior during menstruation among young women at the Al-Quran and Conscience Islamic Boarding School in 2023. Method : This research is quantitative with a cross-sectional method. The population of this study was 132 people. Sampling in this study used the Total Sampling Technique. This research was conducted at the Al-Quran and Conscience Islamic Boarding School in 2023. Results : Statistical tests using the Chi-Square test resulted in a p-value of 0.000. smaller than 0.05 means that Ho is rejected and Ha is accepted. Conclusion : There is a relationship between knowledge and personal hygiene behavior during menstruation among young women at the Al-Quran and Conscience Islamic Boarding School in 2023.